ANALISIS PENGARUH E-WOM, BRAND IMAGE DAN TRUST TERHADAP PURCHASE INTENTION ECO-FRIENDLY TRANSPORT DI SURAKARTA - Hamida Ardianto Muzakar Isa (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
This research aims to test the analysis of the influence of E-Wom, brand image, and trust on purchase intention for eco-friendly transport in Surakarta. Participants in this research who utilise environmentally sustainable modes of transportation in Surakarta. The sample used was users of eco-friendly transport products aged 17 and over, and 309 respondents were domiciled in the Surakarta area. PLS 3.0 analysis was utilised by the researchers to conduct a quantitative examination of the research data. Trust significantly and positively influences the purchase intention of eco-friendly transport users; the brand image variable significantly and positively influences the purchase intention of eco-friendly transport users; e-wom positively and significantly influences the brand image of eco-friendly transport users; and trust significantly and positively influences the purchase intention of eco-friendly transport users.